A facile and mild Pd-catalyzed one-pot process for direct hydrodeoxygenation (HDO) phenols to arenes through a ArOSO2F intermediates transformation. Issue 24 (14th June 2017) - Wang, Xiao-Yan; Leng, Jing; Wang, Shi-Meng; Asiri, Abdullah M.; Marwani, Hadi M.; Qin, Hua-Li
Graphical abstract: A facile and mild process for direct converting phenols to arenes with a wide scope compatibility and functional groups tolerability. Highlights: A one-pot mild process for direct hydrodeoxygenation of phenols to arenes. This method displays wide scope compatibility and functional groups tolerability. This protocol is applicable for hydrodeoxygenation of complicated molecules and multi-phenolic compounds. Abstract: A practical one-pot process for hydrodeoxygenation (HDO) of phenolic derivatives to their corresponding arenes was developed. This method provided a facile route to upgrading bio-oil. The substrate scope of this protocol was wide, complicated and multi-phenolic compounds were also smoothly hydrodeoxygenated to their corresponding arenes.